IMPLIKASI PSAK 38 : KOMBINASI BISNIS ENTITAS SEPENGENDALIAN PADA PENCATATAN LAPORAN KEUANGAN PT MATAHARI PRIMA TBK - Febriyani, Nurindah; Permatasari, Gading Dwi; Uzliawati, Lia (Jurnal Akuntansi Kompetif, 2023)
PSAK 38 is a statement of accounting standards that regulates the accounting treatment of business entities under common control. PSAK 38 was formed to comply with PSAK 22 Business Combinations, creating a business that is carried out in the context of reorganizing entities that are under the same control. The purpose of this study is to compare the application of PSAK 38 (revised 2012) with PSAK 38 (revised 2004) to the combined financial statements of the company PT Matahari Prima Tbk based on previous researchers, as evidence for the application of PSAK 38.